Seeking, accessing, sharing and using information in Brazilian micro and small enterprises - Maia Woida, Luana [UNESP] (My University, 2019)
Information search, access, sharing and needs of entrepreneurs of small and medium-sized enterprises in Brazil was researched using exploratory and descriptive methods. The data was gathered by local innovation agents of the government programme LIA from entrepreneurs of 18 São Paulo Estate cities. Results suggest that there is no information sharing, that access to information is restricted to a small group of employees, and that they do not access information as often as they should, and when they do, they follow informal procedures. In addition, information is underutilized, a lot of information from customers is ignored, and information obtained from the external environment is not used to improve or innovate the business, its products, services and processes. Business processes are not recorded systhematically, making them difficult to access. So, SMEs do not have the systematized information environment that is needed to reach a high degree of innovation.
Busca, acesso, compartilhamento e uso de informação em micro e pequenas empresas do Brasil
Keywords: Brazil; Business information; Information needs; Information sources; Information use; Micro and small enterprises